2005
DOI: 10.1007/s00424-005-1491-6
|View full text |Cite
|
Sign up to set email alerts
|

Roles of PACAP and PHI as inhibitory neurotransmitters in the circular muscle of mouse antrum

Abstract: Mediators of neurogenic responses of the gastric antrum were studied in wild-type and pituitary adenylate cyclase-activating polypeptide (PACAP) -knockout (KO) mice. Electrical field stimulation (EFS) to the circular muscle strips of the wild-type mouse antrum induced a triphasic response; rapid transient relaxation and contraction, and sustained relaxation that was prolonged for an extended period after the end of EFS. The transient relaxation and contraction were completely inhibited by L-nitroarginine and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Besides its effects on the secretory activity of exocrine and endocrine cells, PACAP induces a concentrationdependent relaxation of gastric smooth muscles (Katsoulis et al, 1996;Robberecht et al, 1998;Mukai et al, 2006;Toyoshima et al, 2006), causing a decrease of gastric motility and a delay in stomach emptying (Ozawa et al, 1999). PACAP also exerts a relaxant effect on intestinal smooth muscles from rat (Mungan et al, 1992a;Schwörer et al, 1992;Katsoulis et al, 1993b;Grider et al, 1994;Ekblad and Sundler, 1997;Olsson and Holmgren, 2000), guinea pig (Mungan et al, 1992a;Schwörer et al, 1992;Katsoulis et al, 1993b;Grider et al, 1994;Ekblad and Sundler, 1997;Olsson and Holmgren, 2000) and Atlantic cod, Gadus morhua (Mungan et al, 1992a;Schwörer et al, 1992;Katsoulis et al, 1993b;Grider et al, 1994;Ekblad and Sundler, 1997;Olsson and Holmgren, 2000), thus reducing the motility of the bowel (Lä uff et al, 1999).…”
Section: F Effects Of Pituitary Adenylate Cyclase-activating Polypepmentioning
confidence: 99%
“…Besides its effects on the secretory activity of exocrine and endocrine cells, PACAP induces a concentrationdependent relaxation of gastric smooth muscles (Katsoulis et al, 1996;Robberecht et al, 1998;Mukai et al, 2006;Toyoshima et al, 2006), causing a decrease of gastric motility and a delay in stomach emptying (Ozawa et al, 1999). PACAP also exerts a relaxant effect on intestinal smooth muscles from rat (Mungan et al, 1992a;Schwörer et al, 1992;Katsoulis et al, 1993b;Grider et al, 1994;Ekblad and Sundler, 1997;Olsson and Holmgren, 2000), guinea pig (Mungan et al, 1992a;Schwörer et al, 1992;Katsoulis et al, 1993b;Grider et al, 1994;Ekblad and Sundler, 1997;Olsson and Holmgren, 2000) and Atlantic cod, Gadus morhua (Mungan et al, 1992a;Schwörer et al, 1992;Katsoulis et al, 1993b;Grider et al, 1994;Ekblad and Sundler, 1997;Olsson and Holmgren, 2000), thus reducing the motility of the bowel (Lä uff et al, 1999).…”
Section: F Effects Of Pituitary Adenylate Cyclase-activating Polypepmentioning
confidence: 99%
“…PAC KO studies also demonstrated that PACAP is an important neurotransmitter in mediating GI motility [4648]. Studying PACAP KO mice, PACAP, as well as PHI, were found to function as inhibitory neurotransmitters in the circular muscle of the mouse antrum [4648].…”
Section: Functions/roles Of Vip/pacap and Their Receptors Revealementioning
confidence: 99%
“…Studying PACAP KO mice, PACAP, as well as PHI, were found to function as inhibitory neurotransmitters in the circular muscle of the mouse antrum [4648]. PHI and PACAP mediated sustained relaxation in the gastric antrum [46,46], and PACAP’s action required the activation of a big conductance calcium-activated K+ (BK) channel [48]. …”
Section: Functions/roles Of Vip/pacap and Their Receptors Revealementioning
confidence: 99%
“…The role of endogenous PACAP in the regulation of motility is supported by the inhibition of the sustained relaxation by a PACAP receptor antagonist, PACAP6–38 ( 85 ). Furthermore, muscle strips prepared from PACAP knockout mice showed decreased level of sustained relaxation, which was about one-half of that observed in wild-type mice ( 85 ). PACAP6–38 inhibited electrical field stimulation-induced sustained relaxation (33.5% of control) in PACAP knockout mice.…”
Section: Effects Of Pacap In the Stomachmentioning
confidence: 99%